(untitled) (Research, Society and Development, 2025)
The objective of this research is to present a study that helps to fill a gap in the literature by proposing a maturity model to assess the readiness of Brazilian public health units for the implementation of Digital Twins (DTs). DGs, as part of Industry 4.0 (I4.0) technologies, can optimize resource and process management in healthcare. The model was developed through a systematic review of Critical Success Factors (CSFs) for DG implementation and maturity model dimensions. CSFs were grouped into six conceptual classes, while maturity dimensions were categorized into four: Infrastructure, Organization, Processes, and Information Management—each with four levels: Initial, Basic, Intermediate, and Advanced. Preliminary validation was conducted in basic health units in two cities and two hospitals in the southern Fluminense region of Rio de Janeiro. Results showed the model’s ability to differentiate organizational maturity levels, highlighting its potential for practical application. This study contributes to the field by offering a tailored tool for strategic planning and resource allocation in the implementation of DGs in the public health sector, with possible expansion to private units.